Partial taxonomic revision of Amphoriscus Haeckel, 1870 (Porifera: Calcarea), with description of A. decennis sp. nov. - Chagas, Cléslei; Cavalcanti, Fernanda F. (Zootaxa, 2021)
Amphoriscus is the type genus of the family Amphoriscidae. Since its nomination in the 19th century, its diagnosis has undergone significant changes. Most of the species currently assigned to Amphoriscus have only been reported once, when they were first described. Furthermore, unlike other Amphoriscidae genera, new Amphoriscus species are not commonly described. Therefore, the understanding of the diversity, distribution, and morphology of the genus remains fragmented, a lacuna that is being filled slowly. In this study, several species were revisited by the redescription of type and/or additional specimens. This results in considerable advances, including changes in the geographical distribution of A. cylindrus and A. chrysalis, a proposal of reallocation of A. dohrni in Leuconia, recognition of A. gastrorhabdifera as incertae sedis, a detailed description of the type species based on a set of specimens and, finally, the description of a new species, A. decennis sp. nov.